Rhabdomyolysis following colorectal endoscopic submucosal dissection: A case report - Ying Chen; Wenxuan Zhang; Junqiang Cai; Min Zhong (Clinical Case Reports)
Key Clinical Message The occurrences of rhabdomyolysis after endoscopic submucosal dissection surgery were rarely reported. This is a case involving rhabdomyolysis affecting the muscles of the left buttocks and left hip following a prolonged endoscopic submucosal surgery.